THE EDUCATIONAL POTENTIAL OF JUDO IN THE DEVELOPMENT OF SCHOOLCHILDREN (EDUCATION IN THE 21ST CENTURY, 2023)
Today, sport in its various manifestations - mass, Olympic, disabled, professional, as an effective means of solving health, educational and educative issues of the younger generation, occupies a special place in our society. Field specialists consider sport as an educational environment with a very high socio-pedagogical potential. In this context, judo as a sport and as a pedagogical system, is used by many specialists in school-age children`s comprehensive development process.As a result of studying the directions of the socio-pedagogical impact of judo, researchers suggest using physical education with elements of judo, sports physical education lessons and judo training to increase the level of physical fitness of school-age children, improve their health, form moral qualities, prevent bullying, in order to develop the physical, psychological and social abilities and skills of children with special needs.
Keywords: judo; school-age children; pedagogical influence; physical fitness; health promotion; bullying prevention